2017
DOI: 10.1155/2017/7375818
|View full text |Cite
|
Sign up to set email alerts
|

The LymphotoxinβReceptor Is Essential for Upregulation of IFN-Induced Guanylate-Binding Proteins and Survival afterToxoplasma gondiiInfection

Abstract: Lymphotoxin β receptor (LTβR) signaling plays an important role in efficient initiation of host responses to a variety of pathogens, encompassing viruses, bacteria, and protozoans via induction of the type I interferon response. The present study reveals that after Toxoplasma gondii infection, LTβR−/− mice show a substantially reduced survival rate when compared to wild-type mice. LTβR−/− mice exhibit an increased parasite load and a more pronounced organ pathology. Also, a delayed increase of serum IL-12p40 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 69 publications
1
7
0
1
Order By: Relevance
“…Thus, it is possible conclude that meloxicam and celecoxib induce a pro-inflammatory immune response, which triggers significant reduction in T. gondii infection. Many studies demonstrated the important protective role of IFN-γ, nitrite (Gazzinelli et al, 1994; Lang et al, 2007; Kemp et al, 2013; Koblansky et al, 2013; Behnke et al, 2017; Abreu-Cabral et al, 2018), IL-17A (Kelly et al, 2005), MIF (Ferro et al, 2008; Flores et al, 2008; Terrazas et al, 2010; Gomes et al, 2011, 2018; Barbosa et al, 2014), TNF and IL-6 (Castro et al, 2013; Barbosa et al, 2014, 2015) during infection by T. gondii . Our recent studies showed that IL-6, TNF and MIF are the most important cytokines involved in the immune response to T. gondii in human trophoblast cells, human explants from third trimester and murine maternal-fetal interface, allowing a significant reduction in the vertical transmission of the parasite (Barbosa et al, 2015; Silva et al, 2017; Gomes et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is possible conclude that meloxicam and celecoxib induce a pro-inflammatory immune response, which triggers significant reduction in T. gondii infection. Many studies demonstrated the important protective role of IFN-γ, nitrite (Gazzinelli et al, 1994; Lang et al, 2007; Kemp et al, 2013; Koblansky et al, 2013; Behnke et al, 2017; Abreu-Cabral et al, 2018), IL-17A (Kelly et al, 2005), MIF (Ferro et al, 2008; Flores et al, 2008; Terrazas et al, 2010; Gomes et al, 2011, 2018; Barbosa et al, 2014), TNF and IL-6 (Castro et al, 2013; Barbosa et al, 2014, 2015) during infection by T. gondii . Our recent studies showed that IL-6, TNF and MIF are the most important cytokines involved in the immune response to T. gondii in human trophoblast cells, human explants from third trimester and murine maternal-fetal interface, allowing a significant reduction in the vertical transmission of the parasite (Barbosa et al, 2015; Silva et al, 2017; Gomes et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The immune response to T. gondii infection is predominantly pro-inflammatory (Lang et al, 2007). During infection, cells from innate immunity, such as macrophages, neutrophils, and dendritic cells recognize the parasite by pathogen-associated molecular patterns (Hou et al, 2011; Koblansky et al, 2013; Gorfu et al, 2014) and produce high levels of pro-inflammatory cytokines, such as interleukin (IL)-12, which activates CD4 + T lymphocytes to produce interferon (IFN)-γ, the major cytokine involved in control of T. gondii (Gazzinelli et al, 1994; Kemp et al, 2013; Koblansky et al, 2013; Behnke et al, 2017). In parallel to IFN-γ, other pro-inflammatory cytokines, such as IL-6, tumoral necrosis factor (TNF), IL-17A, IL-2 and macrophage migration inhibitory factor (MIF) also participate significantly in the immunity against T. gondii (Kelly et al, 2005; Castro et al, 2013; Barbosa et al, 2014, 2015; Gomes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…LTβR deficient (LTβR -/-) mice lack of lymph nodes (LNs) and Peyer's patches (PPs) and show reduced numbers of natural killer (NK) and dendritic cells (DCs) as well as impaired immunoglobulin (Ig) affinity maturation (7,8). In infection models, LTβR -/mice show pronounced defects in their immune response against Listeria monocytogenes, Mycobacterium tuberculosis (5), cytomegalovirus (9), LCMV (10) and Zika virus (11) as well as Toxoplasma gondii (T. gondii) (12). In spite of these extensive deficits, not much is known about the exact role of LTβR signaling for an efficient generation of the immune response against pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that other core members of the TNF/TNFR superfamily such as the ligands TNF, LTα which signal via the TNFRI receptor also play an important part in the immune response to T. gondii (25,37,38). However, there is only limited data published on the role of the LTβR: It has been demonstrated that signaling via the LTβR is essential for the up-regulation of mGBPs after T. gondii infection as well as for overall survival (12). Glatman Zaretsky et al have shown that LTβ signaling is important for maintaining intact splenic architecture and, indirectly, for efficient T. gondii specific antibody production (39).…”
Section: Introductionmentioning
confidence: 99%
“…O sistema imune inato responde a infecção através de receptores de reconhecimento padrão (PRR) onde reconhecem os padrões moleculares associados a patógenos (PAMPs), que podem ser divididos em dois grupos: os ligantes de ácido nucléico (DNAs e RNAs) e os não ligantes (lipopolissacarídeos, lipopeptídeos e flagelina) (HOLMLUND et al, 2002;ABRAHAMS et al, 2004;BEHNKE et al, 2017;ZHANG et al, 2017).…”
Section: Resposta Imune a T Gondii: Participação Ativa De Toll Like unclassified